URGENSI PERENCANAAN PEMBELAJARAN DALAM PENINGKATAN PROFESIONALISME GURU - Nurlaila Nurlaila (Sustainable, 2018)
One of the important elements in the learning process is professional educators. In any education system and process, the teacher plays an important role. Students or students may not learn on their own without the guidance and supervision of teachers who are able to carry out their duties well. Then also students may only learn well if the teacher has prepared a positive environment for them to learn. In fact, even though a number of educators have the same profession as educators / teachers, they have differences or vary in their level of professionalism. An educator is said to be a professional, it is not enough just to have a degree or diploma that he has as a requirement. Mastery of absolute learning planning has a professional teacher. Especially in today's fast-paced information era with all its tendencies requiring anticipation and competence of teachers in their profession so that the learning process can produce graduates (output) in accordance with what is needed by the global community.